2014
DOI: 10.1186/1866-1955-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in age-related effects on brain volume in Down syndrome as compared to Williams syndrome and typical development

Abstract: BackgroundIndividuals with Down Syndrome (DS) are reported to experience early onset of brain aging. However, it is not well understood how pre-existing neurodevelopmental effects versus neurodegenerative processes might be contributing to the observed pattern of brain atrophy in younger adults with DS. The aims of the current study were to: (1) to confirm previous findings of age-related changes in DS compared to adults with typical development (TD), (2) to test for an effect of these age-related changes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 57 publications
3
45
0
1
Order By: Relevance
“…Of the 11 studies focusing on AD in DS, 2 included only subjects diagnosed with DS and AD [12,37], whereas the others involved control groups of individuals without AD, without DS, or even without intellectual disabilities. Two studies did not report the exact number of subjects showing signs of dementia or diagnosed with AD [35,46]. In one study [44], organizational problems resulted in 21% of the subjects going undiagnosed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 11 studies focusing on AD in DS, 2 included only subjects diagnosed with DS and AD [12,37], whereas the others involved control groups of individuals without AD, without DS, or even without intellectual disabilities. Two studies did not report the exact number of subjects showing signs of dementia or diagnosed with AD [35,46]. In one study [44], organizational problems resulted in 21% of the subjects going undiagnosed.…”
Section: Resultsmentioning
confidence: 99%
“…However, after detailed analysis of the articles, 3 were excluded: 1 was excluded because it was a postmortem analysis [32], and 2 were excluded because they did not address the diagnosis or signs of dementia [33,34], although 1 of those 2 did address the relationship between oxidative stress and a decline in memory [34]. Therefore, we reviewed 14 articles [12,20,35,36,37,38,39,40,41,42,43,44,45,46], all of which are profiled in table 1. Although we would have included studies available in English, Spanish, Italian, or Portuguese, from the 14 studies, only 1 was in Spanish, the other ones were all in English.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that individuals with DS experience accelerated or an early onset of brain aging as evidenced by significant age-related reduction in brain volume (Beacher et al, 2010;Koran et al, 2014;Teipel et al, 2004). While numerous volumetric studies have characterized the structural brain anomalies associated with DS, less is known about the functional consequences of such structural anomalies in the DS brain.…”
mentioning
confidence: 99%